Comparative Analysis of Service Quality Load Balancing Using NTH and PCC Methods in Internet Access Process - Dian Novianto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The quality of service on the network is very important. To improve internet performance without time constraints, a solution is needed to ensure its availability. One technique that can be used to ensure internet availability is load balancing, this technique works by providing two or more active links to divide data traffic between links, so that if one link dies or overloads it can be diverted to other links evenly. In this study, the methods that will be used as load balancing techniques are NTH and PCC. While the research methodology used is qualitative and comparative, where the comparative method will compare the results of testing load balancing techniques using the NTH and PCC methods. Testing is carried out by means of downloading files in sizes 100 MB and 100 MB. For QoS performance analysis based on parameters: delay, jitter packet loss and throughput. The results of the best Quality of Service (QoS) load balancing after being tested and compared based on predetermined parameters resulted in the conclusion that the NTH method was slightly better than PCC.